2012
DOI: 10.1194/jlr.d029546
|View full text |Cite
|
Sign up to set email alerts
|

Saturated fatty acids activate TLR-mediated proinflammatory signaling pathways

Abstract: Toll‐like receptor 4 (TLR4) and TLR2 were shown to be activated by saturated fatty acids (SFAs) but inhibited by docosahexaenoic acid (DHA). However, one report (ATVB 11:1944, 2009) suggested that SFA‐induced TLR activation in cell culture systems is due to contaminants in BSA used for conjugating fatty acids. This report casted doubt about proinflammatory effects of SFAs. Our studies herein demonstrate that sodium palmitate (C16:0) or laurate (C12:0) without BSA conjugation induced phosphorylation of IκBα, JN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
373
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(410 citation statements)
references
References 45 publications
19
373
2
7
Order By: Relevance
“…[12,87,88] In particular, elevated plasma levels of NEFAs are frequently observed in patients with MetS and visceral obesity [52] ; NEFAs may promote endothelial dysfunction, the first step of atherosclerosis, by immune activation and upstream regulation of the nuclear transcription factor kappa B (NFκB). [87] By triggering NFκB, [89] saturated fatty acids such as palmitate (16:0) and stearate (18:0), promote crucial events in the initial steps of atherogenesis. [90] They enhance the adherence and transmigration of monocytes and lymphocytes by increasing the expression of cell adhesion molecules (ICAM-1, VCAM-1, and Eselectin), upregulating the expression of inflammatory cytokines (TNF-α, IL-6, and IL-8), and promoting apoptosis of endothelial cells.…”
Section: Atherosclerosismentioning
confidence: 99%
“…[12,87,88] In particular, elevated plasma levels of NEFAs are frequently observed in patients with MetS and visceral obesity [52] ; NEFAs may promote endothelial dysfunction, the first step of atherosclerosis, by immune activation and upstream regulation of the nuclear transcription factor kappa B (NFκB). [87] By triggering NFκB, [89] saturated fatty acids such as palmitate (16:0) and stearate (18:0), promote crucial events in the initial steps of atherogenesis. [90] They enhance the adherence and transmigration of monocytes and lymphocytes by increasing the expression of cell adhesion molecules (ICAM-1, VCAM-1, and Eselectin), upregulating the expression of inflammatory cytokines (TNF-α, IL-6, and IL-8), and promoting apoptosis of endothelial cells.…”
Section: Atherosclerosismentioning
confidence: 99%
“…How fatty acid species other than oleic acid might affect amino acid transport remains to be established. However, in other tissues, it has been shown that different fatty acid species modulate TLR4 signaling differently, with saturated fatty acids activating and polyunsaturated fatty acids inhibiting TLR4 signaling ( 10,11 ). TLR4 was required for oleic acid to stimulate amino acid transport, and oleic acid activated JNK and STAT3.…”
Section: Silencing Tlr4 Prevents Oleic Acid Stimulation Of System a Amentioning
confidence: 99%
“…An increasing amount of literature shows that fat‐induced alterations in T cell lineages and the activation status of macrophages and microglia exacerbate neuroinflammation in MS and the EAE model 98, 99, 100, 101, 102, 103. Interestingly, excessive fat consumption is also a key factor inducing obesity, which increases the risk of developing MS 60, 61, 62.…”
Section: Involvement Of Fatty Acids In Cns Autoimmunity: Saturated Vementioning
confidence: 99%
“…Endotoxins can promote T H 1 and T H 17 polarization,106, 107 as well as the inflammatory activation of peripheral and CNS‐resident innate immune cells 108, 109. Of interest, SFAs, such as palmitate (C16:0) and laurate (C12:0), can also directly activate TLR‐mediated proinflammatory signaling pathways in innate immune cells 100. Finally, while feeding dietary monounsaturated fats reduces low‐density lipoprotein (LDL) levels, SFAs are reported to elevate circulating LDL 110.…”
Section: Involvement Of Fatty Acids In Cns Autoimmunity: Saturated Vementioning
confidence: 99%